(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article identifies crucial milestones for the development of Theatre for Young Audiences (TYA) during the 2000s in Chile. A synthetic vision of the history of TYA in the country is presented, recognising, based on Bourdian notions, a tension between educational objectives and artistic objectives implied in the delegitimization of this type of creations. The article analyses interviews with significant agents of the period to discuss how these milestones contributed to the legitimation of TYA in the Chilean theatre field, seeking a balance between education and art and emphasizing respect for the capacities of their audiences to have valuable aesthetic experiences.